FRI0403 Heart Valvular Involvement in the Antiphospholipid Syndrome. An Echocardiographic Descriptive Study. (9th June 2015) - Pons, I.; Louro, J.; Espinosa, G.; Azqueta, M.; Paré, C.; Sitjes, M.; Cervera, R.
Abstract : Background: Valvular involvement is the most common cardiac manifestation in the antiphospholipid syndrome (APS) and has been associated to high risk of arterial thrombotic events, presence of cardiovascular risk factors, livedo reticularis and migraine. Objectives: To describe the prevalence, clinical features and evolution of APS patients with heart valvular involvement followed in a single center. In addition, we determined the association between heart valve disease and different demographic, clinical and laboratory features in patients with APS. Methods: A retrospective longitudinal and observational study of all patients diagnosed according to current classification criteria of APS in which at least, one transthoracic echocardiographic study was performed. Descriptive analysis of echocardiographic findings, demographic, previous clinical characteristics, laboratory features and evolution was considered. Results: 128 APS patients were included. 66 of them (51.6%) presented valvular involvement. Among them, 57 (86.4%) were women and the mean age at the onset of symptoms was 38.8±16 years (range 18-71). 45 (68.2%) had primary APS whereas 21 (31, 8%) presented an associated-SLE APS. 35 (53%) presented with at least one cardiovascular risk factor. 58 (87.9%) pacients have had a thrombotic event, of which 19 (32.8%) were venous, 37 (63.8%) arterial, and 2 (3.4%) both. Main findings found in echocardiographic study were mitral thickening in 48 (72.7%) cases, mitral insufficiency in 46 (69.7%), mitral regurgitation in 43 (65.1%), tricuspid regurgitation and tricuspid insufficiency in 26 (39.4%), nonbacterial thrombotic endocarditis in 25 (36.2%) (20 (80%) on mitral valve and 5 (20%) on aortic valve), aortic thickening in 17 (25.8%), aortic insufficiency in 15 (22.7%) and tricuspid thickening, mitral stenosis and aortic stenosis in 1 (1.5%) each. 10 (15.1%) required valve replacement surgery, 8 (80%) on mitral valve and 2 (20%) on aortic valve. Lupus anticoagulant was the antiphospholipid antibody most frequent, present in 56 (84.8%) pacients, followed by anticardiolipin antibodies in 52 (78.8%), having double positivity 42 (63.6%). 9 (13.6%) patients died during follow-up. Multivariate analysis identified a significant statistically differences in heart valve involvement group in a greater proportion of women (p=0.002), the presence arterial hypertension (p=0.018), arterial thrombosis (p=0.007), stroke (p=006) and livedo reticularis (p=0.017), and a less number of venous thrombosis (p=0.018), as well as fewer episodes of deep venous thrombosis in lower extremities (p=0.035). The presence of lupus anticoagulant (p=0.014) and the absence of antinuclear antibodies (p=0.011) were the significant differences in laboratory features. Also, the valve involvement group was associated with higher mortality (p=0.018). Conclusions: Heart valve disease is a frequent manifestation in our cohort of patients with APS, and is associated with demographic, clinical and laboratory features and increased mortality. More studies are needed, but our results support the hypothesis that there may be a subgroup of patients with APS and valve involvement with its own characteristics that differentiated the rest of patients with APS. Disclosure of Interest: None declared